Differential Outcomes of Sleep Problems in Children with and Without Special Health Care Needs: Australian Population Study. Issue 5 (June 2016) - Quach, Jon; Mensah, Fiona K.; Hiscock, Harriet
ABSTRACT: Objective: In a nationally representative sample of Australian children at ages 4 to 5, 6 to 7, 8 to 9, 10 to 11, and 12 to 13 years, we aim to examine the (1) prevalence of sleep problems in children with and without special health care needs (SHCN); (2) association of sleep problems with child behavior, health-related quality of life, learning and parent mental health outcomes; and (3) whether associations between sleep problems and outcomes among children with SHCN are larger in magnitude than among children without SHCN. Method: Biennial data from 5 waves of the Growing Up in Australia Study. Exposures: Child SHCN as defined by the Children Special Health Care Needs Screener and parent report of child sleep problem . Outcomes: Child: parent-reported health-related quality of life; parent-reported and teacher-reported behavior; nonverbal and verbal cognition and teacher-reported learning. Parent: self-report mental health. Analysis: Logistic and linear regression, adjusted for family socioeconomic position. Results: Children with SHCN were more likely to have sleep problems, odds ranging from 2.0 (95% confidence interval [CI], 1.6–2.5) at 4 to 5 years to 3.9 (95% CI, 3.0–5.2) at 8 to 9 years. Compared with children who had neither condition, those with either sleep problems or SHCN had similarly poor child and maternal outcomes. Children with both SHCN and sleep problems had the poorest outcomes at every age (all p < .001). Tests of interaction found sleep problems are more strongly associated with poorer behavior and health-related quality of life among children with SHCN than those without during the preschool and early school years. Conclusion: Sleep problems in children with SHCN are common and are associated with poorer child and maternal outcomes. These associations are stronger for poorer behavior and health-related quality of life among children with SHCN than those without during the preschool and early school years.